Increased Sensitivity of the Microbiological Assay for Biotin by Lactobacillus plantarum - Waller, James R. (1970)
Addition of Tween 80 to biotin assay medium containing acid-hydrolyzed casein as the amino acid source caused marked growth of Lactobacillus plantarum ATCC 8014 in the absence of added biotin. This growth-promoting activity could be eliminated by treating the “vitamin-free” Casamino Acids (Difco) with activated charcoal (Darco G-60) at pH 3.5 for 30 to 60 min. Incorporation of Tween 80 and charcoal-purified Casamino Acids (PCA) into the assay medium (0.8 g and 27 g, respectively, per liter of single strength medium) in place of unpurified Casamino Acids resulted in a medium in which L. plantarum responded to 30 to 50 times less biotin over an extended linear response range (1.3 logs versus 1.0 log) than was required for similar growth in the standard medium. Endogenous growth in the modified medium was absent if the inoculum used was of low density, if it was prepared from biotin-deficient cells, and if the reagents used were free from contaminating traces of biotin. Assays of biological materials for biotin content using the standard medium and the Tween 80-PCA-modified medium resulted in nearly identical values for all samples tested.